2016
DOI: 10.14789/jmj.62.399
|View full text |Cite
|
Sign up to set email alerts
|

The Usefulness of Measuring Anti-Xa Activity for the Prediction of Bleeding Adverse Events During Postsurgical Fondaparinux Anticoagulant Therapy

Abstract: Objective: Anticoagulation therapy is commonly used to prevent venous thromboembolism after abdominal surgery. However, bleeding during anticoagulation therapy is a problem, particularly in use of fondaparinux (FPX), for which there is no useful monitoring method. In this study, we examined the usefulness of measurement of the inhibitory activity of activated blood coagulation factor X (anti-Xa activity) for prediction of bleeding. Subjects and Methods:The subjects were 67 patients who underwent anticoagulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…A previous study indicated that enoxaparin did not increase the risk of postoperative bleeding 29. Niwa et al reported that anticoagulant therapy with fondaparinux, which is also a low-molecular-weight heparin, increased the incidence of gastrointestinal bleeding after surgery and that anti-Xa factor activity measurements might be useful for predicting bleeding 36…”
Section: Discussionmentioning
confidence: 99%
“…A previous study indicated that enoxaparin did not increase the risk of postoperative bleeding 29. Niwa et al reported that anticoagulant therapy with fondaparinux, which is also a low-molecular-weight heparin, increased the incidence of gastrointestinal bleeding after surgery and that anti-Xa factor activity measurements might be useful for predicting bleeding 36…”
Section: Discussionmentioning
confidence: 99%